ANALISIS MOTIVASI BELAJAR DAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA KELAS VIII SMP SWASTA KRISTEN BNKP TELUKDALAM TAHUN PEMBELAJARAN 2021/2022 - Wehalo, Florentina (Universitas Nias Raya, 2023)
This research uses a type of qualitative research with a descriptive research approach. The informants of this study were students of class VIII-A Christian Private Middle School BNKP Telukdalam, which consisted of 32 students. Data were analyzed by the steps of data collection, data reduction, data presentation and drawing conclusions. The research instruments used were questionnaires, problem-solving ability tests and interviews. The research findings showed that: Of the 32 students, there were 12.5% ​​of students in the very good category, 40.6% of students in the good category, 46.9% of students in the medium category, and there were no students in the less or very poor category. The highest percentage for each indicator of student learning motivation is: the desire and desire to succeed (enough category, 50.0%), the encouragement and need for learning (good category, 53.1%), the existence of hopes and aspirations for the future (good category, 53.1%), there is appreciation in learning (good category, 56.3%), there are interesting activities in learning (enough category, 53.1%), there are conducive learning activities (enough category, 50 and 15.63% of students in the very less category. Through this research, the researchers suggest that teachers should create a pleasant atmosphere for learning mathematics, involve students so that they can motivate students to learn mathematics and provide habituation to students in solving mathematical problems using the correct procedures or steps for solving them.